2018
DOI: 10.1021/acs.jafc.8b03901
|View full text |Cite
|
Sign up to set email alerts
|

Heating-Aided pH Shifting Modifies Hemp Seed Protein Structure, Cross-Linking, and Emulsifying Properties

Abstract: Alkaline pH 12 shift treatment performed at varying temperatures (20−80 °C for 1, 5, and 60 min) was applied to structurally modify hemp seed protein isolate (HPI). The solubility of HPI (∼20%) was remarkably improved (p < 0.05) with elevating the temperature and prolonging the holding time, reaching 97.5% at 80 °C for 60 min. The treated HPI exhibited a strong tendency of forming soluble large aggregates. To limit lysinoalanine (LAL) production, heating was methodically controlled to 60 °C and 5 min, where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(69 citation statements)
references
References 43 publications
6
61
1
1
Order By: Relevance
“…It should be noted that adverse chemical reactions, such as the conversion of cysteine and serine residues to nephrotoxic lysinoalanine compounds, can occur under highly alkaline and heating conditions. As reported by Wang, Jin, and Xiong (2018), HPI extracted at pH 10 and room temperature had a low level of lysinoalanine (0.8 mg/100 g protein). However, if the extracted HPI was held at pH 12 for as short as 5 min at 40°C, the lysinoalanine content would increase to 4 mg/100 g protein.…”
Section: Protein Processingsupporting
confidence: 71%
See 3 more Smart Citations
“…It should be noted that adverse chemical reactions, such as the conversion of cysteine and serine residues to nephrotoxic lysinoalanine compounds, can occur under highly alkaline and heating conditions. As reported by Wang, Jin, and Xiong (2018), HPI extracted at pH 10 and room temperature had a low level of lysinoalanine (0.8 mg/100 g protein). However, if the extracted HPI was held at pH 12 for as short as 5 min at 40°C, the lysinoalanine content would increase to 4 mg/100 g protein.…”
Section: Protein Processingsupporting
confidence: 71%
“…However, Wang et al. () found that heating at 80 °C up to 60 min actually slightly improved the solubility of HPI (Figure ). The discrepant findings may be due to different protein concentration testing methods, as well as the protein composition.…”
Section: Structural Modification For Functionality Improvementmentioning
confidence: 97%
See 2 more Smart Citations
“…Jiang, Chen, and Xiong (), Valenzuela, Abugoch, Tapia, and Gamboa (), and Wang, Jin, and Xiong () observed for soybean, quinoa, and hemp proteins, respectively, that a shift to pH 12 caused protein unfolding through changes mainly in their tertiary structure. This unfolding allowed the exposure of hydrophobic groups, and the formation of large aggregates involving disulfide bonds (>1000 kDa for quinoa).…”
Section: Resultsmentioning
confidence: 98%